2019
DOI: 10.9775/kvfd.2019.22058
|View full text |Cite
|
Sign up to set email alerts
|

İçme Suyu Katkısı Olarak Kullanılan Myrtus communis L. Bitki Özütünün Yaşlı Yumurtacı Tavuklarda Performans, Bazı Kan Parametreleri, Yumurta Kalitesi ve Bağışıklık Tepkisi Üzerine Etkileri

Abstract: The aim of the present study was to evaluate the effects of myrtle plant extract (MPE) on performance, some blood parameters, egg quality and immune response of older laying hens. A total of 192 laying hens (67 weeks old; initial body weight 1.63±0.17 kg) were used in this study. The MPE was added to the water of the experimental groups (0%, 2.5%, 5.0%, or 10%) for 8 weeks. Liquid chromatography analyses showed that myricetin was the predominant active ingredient (15.34 mg/L) in MPE. In treatment groups, feed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…There was no effect on the artificial insemination and conception rate ( Table 4 ). Previous studies have reported similar positive effects, such as increased feed consumption and egg production in laying hens when myrtle plant extract was added to drinking water at different concentrations [ 12 ]. Consistent with these findings, Bardzardi et al [ 10 ] observed increased feed consumption and live weight in broilers when myrtle extract was added to the rations.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…There was no effect on the artificial insemination and conception rate ( Table 4 ). Previous studies have reported similar positive effects, such as increased feed consumption and egg production in laying hens when myrtle plant extract was added to drinking water at different concentrations [ 12 ]. Consistent with these findings, Bardzardi et al [ 10 ] observed increased feed consumption and live weight in broilers when myrtle extract was added to the rations.…”
Section: Resultsmentioning
confidence: 81%
“…Administering different amounts of myrtle plant extract with milk to calves resulted in reduced blood glucose values in the MPEL-50 and MPER-50 groups. In a similar study [ 12 ], blood glucose concentration in laying hens, where 2.5%, 5% and 10% of myrtle plant extract were added to their drinking water, were found to be lower in all trial groups compared to the control group. Researchers attribute the hypoglycemic effect observed in the experimental groups to myricetin, the most abundant active ingredient in the myrtle plant extract.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation